Blends and Graft Copolymers of Cellulosics : Toward the Design and Development of Advanced Films and Fibers - Nishio, Yoshiyuki; Teramoto, Yoshikuni; Kusumi, Ryosuke; Sugimura, Kazuki; Aranishi, Yoshitaka (Springer International Publishing : Imprint: Springer, 2017)
This book reveals how polymer blending and grafting now offer a growing range of new applications for advanced films and fibers. Further, it details how the processing and original physical properties of cellulosics can be improved, and demonstrates how new, cellulose-core polymeric materials offer a wide range of synergistic functionalities. Lastly, it summarizes basic characterization studies and successful fabrications of advanced films and fibers. The book is primarily intended for advanced undergraduates, academic and industrial researchers and professionals studying or using bio-based polymers.
Keywords: Materials science.; Carbohydrates.; Polymers.; Nanotechnology.; Biomaterials.; elektronické knihy; electronic books